Study on the Oil Distribution and Churning Loss in the Rotation of a Planetary Gear Train - Chen Huixiao; Shi Lubing; Zhi Yanfeng; Yan Shidang; Ding Haohao; Pei Bang; Liu Zhongming; Wang Wenjian (Jixie chuandong)
A splash lubrication simulation model of a planetary gear train was established based on the moving particle semi-implicit （MPS） method, and it was verified by experiments to explore the splash lubrication behavior of the planetary transmission. Through the simulation, the oil distribution characteristics, the number of lubricating oil particles in the engagement zones, and the churning loss of the rotating components were studied. The results show that in the rotation of the planetary gear train, the interior space of the gearbox can be divided into three regions: the oil-pool region, the oil-dragging region, and the oil-poor region. The number of oil particles in different engagement zones and the churning torque of each component show periodic variations during the planet gear passes through the three regions. The numbers of oil particles in the inner and outer engagement zones reach the peak when the planet gear runs into the oil-pool region, and both drop rapidly to a minimum value after entering the oil-poor region. The churning torque of the planet gear rises sharply to the peak after entering the oil-pool region and keeps the peak value until the planet gear enters the oil-dragging region, then the churning torque turns to fall until stabilizing at a very low level when the planet gear enters the oil-poor region. Different from the planet gear, the churning torque of the planetary frame drops sharply when one of the planet gears enters the oil-pool region and rises rapidly when that planet gear enters the oil-dragging region and the next one has not entered the oil-pool region. The churning torque of the sun gear is small and insensitive to the planet gear positions. Among the total churning power of the planetary gear train, the sum of the three planet gears accounts for about 60%, followed by the planetary frame, and the sun gear accounts for the least.